Reinvestigating the Co-Movements between Stock Market and Exchange Rates: An Augmented Vector Autoregression Analysis - Akinkunmi, Mustapha Abiodun; Bello, Saheed (The Economics and Finance Letters, 2022)
Empirical works on the stock market exchange rate nexus remain scanty in the managed floating exchange rate environment like Nigeria. Thus, our paper contributes to the scanty literature by analyzing how the COVID19 pandemic shapes the existing link in the oil-rich countries like Nigeria using a time series approach based on daily data spanning between 2017 and 2021. The paper investigates a Granger causality relationship in the specified VAR model by implementing the Toda and Yamamoto procedures while determining the direction of the causality through our impulse response analysis. Our findings show unidirectional causality from exchange rates to the stock market in the pandemic but no causality before the pandemic. This suggests that the exchange rate affects the performance of the Nigerian stock market in the pandemic period. Therefore, the Nigerian stock market and the exchange rate should not be considered as alternative strategies to mitigate risk during the crisis periods.